Clinical criteria and the appropriate use of transthoracic echocardiography for the exclusion of infective endocarditis. Issue 3 (1st March 2003) - Greaves, K; Mou, D; Patel, A; Celermajer, D S
Abstract : Background: Clinical guidelines currently suggest that transthoracic echocardiography (TTE) be carried out in all patients with suspected endocarditis, but the use of TTE where there is a low probability of infective endocarditis has a poor diagnostic yield. This screening approach may no longer be appropriate. Objective: To examine whether clinical criteria might aid decision making with respect to the use of TTE in possible endocarditis. Design: A retrospective review of patient records. Setting: Cardiology department of a tertiary referral centre. Patients: 500 consecutive hospital inpatients referred for TTE to exclude endocarditis. Main outcome measures: Evidence of endocardial vegetations on TTE and the presence of predetermined clinical criteria that may predispose to, or be suggestive of, endocarditis. Results: Evidence of infective endocarditis was detected on echocardiography in 43 of the 500 patients (8.6%). In 239 patients (48%), vegetations and certain prespecified clinical criteria were both absent. These criteria were: vasculitic/embolic phenomena; the presence of central venous access; a recent history of injected drug use; presence of a prosthetic valve; and positive blood cultures. The collective absence of these five criteria indicated a zero probability of TTE showing evidence of endocarditis. Conclusions: The use of simple clinical criteria during the decision making process may avoid many unnecessary TTE examinations in hospital inpatients with a low probability of endocarditis.